Interaction impact of cash flow volatility and fixed assets on debt maturity structure in MENA and African countries - Abdulrahman Naser; Bolaji Tunde Matemilola; A. N. Bany-Ariffin (Cogent Business & Management, 2024)
The empirical literature on the association of cash flow volatility and debt maturity structure is limited and inconclusive. This article investigates the impact of cash flow volatility on debt maturity structure, and the interaction effect of cash flow volatility and fixed assets on debt maturity structure. This article applies the two-step system generalized method of moments (GMM) method and uses 1672 non-financial public listed firms for a 10-year period starting from 2011 to 2020. The findings indicate a significant negative association between cash flow volatility and debt maturity structure of firms in Middle East and North Africa (MENA) and African countries. Moreover, the interaction of cash flow volatility and fixed assets is significantly and negatively related to debt maturity structure in MENA and African countries. These findings suggest the need for firm-managers to effectively manage the cash flow risk and consider collateral benefits of fixed assets when choosing the debt maturity structure.
Keywords: 650; Debt structure; cash flow risk; pecking-order theory; panel data; system-GMM; developing countries